Investigation of feasibility of Auto Tuning Vibration Absorber - Näkne, Andreas (My University, 2018)
The thesis is an investigation of the Auto Tuning Vibration Absorber (ATVA) developed by Swerea IVF. Main focus is to improve the absorber so it becomes active for more frequencies and thereby get a more stable behavior and also to adapt it for different systems. Here the focus is on three systems; a pneumatic breaker, a test rig and a reciprocating saw. The investigation is made mainly by performing simulations in MATLAB, but also experiments on the test rig. To find out how stable the systems are the simulations are done in three different ways; one with increasing frequency, one with decreasing frequency and one with each frequency by itself. The experiments were done in different ways, but only with increasing and decreasing frequencies. The ATVA consists of an auxiliary mass that shall counteract the vibrations from the main mass with help of a nonlinear spring system. Earlier it has been a gap between the main mass and the auxiliary mass which makes the masses to not be in contact all the time and this has given the system an unstable behavior, especially when working horizontally without affect of the gravity. To get it more stable it is tested to decrease the gap or to add a spring instead of the gap. This is shown to be very successful and give the system a more stable behavior without worsen other results as much. But the springs and gap needs to be carefully tuned for the systems to work well in their working frequency and to keep the advantages that the nonlinearity has. Keywords: Auto Tuning Vibration Absorber, nonlinear springs, impact machines.
Keywords: Teknisk mekanik; Produktionsteknik, arbetsvetenskap och ergonomi; Produktion; Applied Mechanics; Production Engineering, Human Work Science and Ergonomics; Production